Needle-Assisted Laparoscopic Inguinal Hernia Repair in Children: Experience in Chittagong, Bangladesh (Bangladesh Journal of Endosurgery, 2013)
Purpose: There are numerous procedures of minimally invasive surgery for repair of inguinal hernia in children including percutaneous techniques. We describe here our technique of using 18G or 20G needle in a very simple and effective way for this purpose.Methods: Needle-assisted laparoscopic percutaneous repair internal ring was performed in 55 children between 1st November 2010 and 31st July 2011. An 18G or 20G needle and a 3/0 polyglycolic acid thread were used. A 5-mm supraumbilical port for 30? 5 mm telescope and a 3-mm port in iliac fossa opposite to the lesion to handle the thread intra-abdominally were used.Results: Age ranged from 3 months to 12 years and 40 were males. Seven cases were bilateral making total 62 lesions. Mean operating time was 30.54 ± 5.84 min (range 2042) and there was no intraoperative complication. Postoperatively five cases had transient hydrocele which resolved spontaneously. One case recurred after 2 months.Conclusions: Needle-assisted laparoscopic inguinal hernia repair in children is a simple and effective technique that can be performed routinely in resource poor countries.DOI: http://dx.doi.org/10.11593/bje.2013.0102.0011Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 7-10